Teaching Better : Igniting and Sustaining Instructional Improvement. - Ermeling, Bradley A. (SAGE Publications, 2016)
Discover the power of collaborative inquiry! This unique, visually stunning resource is packed with details to ignite and sustain the collaborative improvement of teaching and learning. Includes US and international case studies, powerful metaphors, application exercises, a leader's guide, a companion website, digital templates, and more. Learn what lesson study and collaborative inquiry can and should look like. Find the guidance you need to lead and support schoolwide, inquiry-based improvement! "A true inspiration for educators who want to improve both their own craft and the methods of t.